PENERAPAN APLIKASI GOOGLE MEET DALAM PEMBELAJARAN BIOLOGI SMA YAYASAN PERGURUAN KELUARGA PADA MASA PENDEMI COVID-19 - Kesumawati, Hapsah; Damanik, Risjunardi; Siboro, Thiur Dianti (Jurnal Metabio, 2024)
This study aims to determine the supporting and inhibiting factors for the implementation of the Google Meet application in biology learning at Yayasan Perguruan Keluarga High School during the Covid-19 Pandemic. This study is a qualitative descriptive type with data collection techniques through interviews, observations, and documentation. The results of this study indicate that the inhibiting factors for the biology learning process during the Covid-19 pandemic are the internet network, student absence during online learning, students' economic conditions, and ownership of gadgets or laptops. The supporting factors are technology, a place to study in accordance with the Covid-19 health protocol, adequate learning resources, and adequate facilities and infrastructure. In conclusion, 95% of the implementation of the Google Meet application in biology learning at Yayasan Perguruan Keluarga High School during the Covid-19 Pandemic was stopped in cycle III, activities had been carried out and learning objectives had been achieved. The Google Meet application can be accepted in online learning, besides the benefits are also optimal and facilitate learning activities.